2002
DOI: 10.2527/2002.8061489x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental parameters for steer ultrasound and carcass traits1

Abstract: Carcass measurements for weight, longissimus muscle area, 12-13th-rib fat thickness, and marbling score, as well as for live animal measurements of weight at the time of ultrasound, ultrasound longissimus muscle area, ultrasound 12-13th-rib fat thickness, and ultrasound-predicted percentage ether extract were taken on 2,855 Angus steers. The average ages for steers at the time of ultrasound and at slaughter were 391 and 443 d, respectively. Genetic and environmental parameters were estimated for all eight trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
53
16
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 15 publications
24
53
16
7
Order By: Relevance
“…Diversos autores observaram valores superiores aos do presente estudo para as médias de AOL e inferiores para EGS (Turner et al, 1990;Arnold et al, 1991;Moser et al, 1998;Kemp et al, 2002) efeito mais pronunciado observado através do processo de engorda. Ainda segundo o mesmo autor, a taxa de acúmulo de gordura nos machos inteiros é menor do que nos novilhos, que por sua vez é menor do que nas novilhas.…”
Section: Resultsunclassified
“…Diversos autores observaram valores superiores aos do presente estudo para as médias de AOL e inferiores para EGS (Turner et al, 1990;Arnold et al, 1991;Moser et al, 1998;Kemp et al, 2002) efeito mais pronunciado observado através do processo de engorda. Ainda segundo o mesmo autor, a taxa de acúmulo de gordura nos machos inteiros é menor do que nos novilhos, que por sua vez é menor do que nas novilhas.…”
Section: Resultsunclassified
“…Several authors, studying Hereford, Brangus, Angus, and Santa Gertrudis breeds, found higher values for REA and lower values for BFT (Turner et al, 1990;Arnold et al, 1991;Moser et al, 1998;Kemp et al, 2002) in animals with 320-369 days of age that were supplemented and mostly male. Values observed in these studies were between 47.46 and 86.0 cm 2 for REA and from 0.47 to 0.95 mm for BFT.…”
Section: Resultsmentioning
confidence: 99%
“…Aplicações principais da ultrasonografia em tempo real na ciência animal como metodologia de estimativa in vivo da composição da carcaça; 1) em programas de seleção de reprodutores para características de qualidade da carcaça e da carne (Brethour, 1992;Lo et al, 1992;Kemp et al, 2002; 2) manejo alimentar e treinamento de avaliação da condição corporal (Delfa et al,1991;Domecq et al,1995, bem como na validação da metodologia de avaliação da condição corporal (Schwager-Suter et al, 2000;Cadavez et al, 2002ª;Bueno et al, 2003; 3) na definição do ponto ótimo de abate (Kempster e Owen,1982;Fuller et al,1990 ;Houghton e Turlington, 1992;Stanford et al, 1998 GÊNOVA, L.G. e DUARTE, K.M.R.…”
Section: Quanto Ao Modo De Disposição Dos Ecos Existem Três Modos Denunclassified